Policy Think Tank (PTT): institutional visit report on policy research and agroecology farming in Vietnam - Inphonephong, Souphalack; Phounvisouk, L.; Sonethavixay, Sengphachanh; Maniphet, P.; Soulinh, T.; Vanhnalat, B.; Sisengnam, K.; Vongthilath, S. (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2023)
The report documents the institutional meetings and discussions taking place between 26-30 November 2023 when a delegation from Lao PDR visited Vietnan. Overall aim of the visit was to enhance institutional cooperation between policy researchers and policy makers for more effective policy formulation. The Lao team learnt about options to strengthen policy implementation, like through formulating specific strategies, supporting farmers to adopt suitable technologies/innovations, and bringing research evidence into the policy formulation process. As the term “agroecology” is new to some stakeholders links to existing practices have to be shown, accompanied by advocating its benefits from a broader view perspective.